2021
DOI: 10.16882/hortis.882469
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Antioxidant Activity and Total Phenolic Content during the Eight-Week Fermentation of Apple Cider Vinegar

Abstract: Apple is one of the delicious fruit consumed by people. Apple cider vinegar was made through the traditional method and the changes occurred during the 8 week fermentation period were determined in this research. Total titratable acidity, pH, total soluble solids (°brix), total phenolic contents, Oxygen Radical Absorbance Capacity (ORAC) and Trolox Equivalent Antioxidant Capacity (TEAC) assays, phenolic contents were determined. Total phenolic substance, ORAC and TEAC values increased significantly weekly and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…This result met the aim of the study to produce a product with higher bioactive compounds than the substance used. Furthermore, when the persimmon vinegar was examined according to some kinds of vinegar in the literature, the amounts of the gallic acid and the chlorogenic acid compounds of this vinegar were higher than apple cider vinegar (Budak, 2021; Kelebek et al, 2017), which is popular for its health benefits, grape vinegar (Budak & Guzel‐Seydim, 2010) and sour cherry vinegar (Özen et al, 2020), which was determined to have significant effects on health. Whereas, it has well been known that vinegar; such as apple cider, grape vinegar, sour cherry vinegar, has been rich in gallic acid, which has a protective effect against many degenerative diseases such as cardiovascular, gastrointestinal, neuropsychological, and metabolic (like obesity, diabetes mellitus, and hyperlipidemia) diseases, and also types of cancers and strains of pathogenic microorganisms (Kahkeshani et al, 2019), and chlorogenic acid, which have a protective effect against cardiovascular diseases with inhibition of LDL oxidation, in addition to many physiological functions, including antimutagenic, carcinogenic and antioxidant activities (Wicklund et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…This result met the aim of the study to produce a product with higher bioactive compounds than the substance used. Furthermore, when the persimmon vinegar was examined according to some kinds of vinegar in the literature, the amounts of the gallic acid and the chlorogenic acid compounds of this vinegar were higher than apple cider vinegar (Budak, 2021; Kelebek et al, 2017), which is popular for its health benefits, grape vinegar (Budak & Guzel‐Seydim, 2010) and sour cherry vinegar (Özen et al, 2020), which was determined to have significant effects on health. Whereas, it has well been known that vinegar; such as apple cider, grape vinegar, sour cherry vinegar, has been rich in gallic acid, which has a protective effect against many degenerative diseases such as cardiovascular, gastrointestinal, neuropsychological, and metabolic (like obesity, diabetes mellitus, and hyperlipidemia) diseases, and also types of cancers and strains of pathogenic microorganisms (Kahkeshani et al, 2019), and chlorogenic acid, which have a protective effect against cardiovascular diseases with inhibition of LDL oxidation, in addition to many physiological functions, including antimutagenic, carcinogenic and antioxidant activities (Wicklund et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…However, the subsequent acetic fermentation provided a significant increase (+20.1%) of total phenolic content in Khistawi date vinegar, reaching a peak value of 1453.4 mg GAE/L during 14 days of fermentation [33]. The increase in phenolic compounds in vinegar brewing, observed by several authors, could be due to two different reasons [85][86][87]. First, the acids produced during acetic fermentation could degrade the glucoside bonds of the phenolic compounds, leading to the liberation of compounds with different structure [33,88].…”
Section: Vinegarmentioning
confidence: 99%
“…n.d.: not detected. Budak (2015) reported that TEAC and TPC values of pomegranate vinegar were between 16-20 µmol/ml and 1200-2200 mg GAE/L, respectively. Özen et al…”
Section: Titration Aciditymentioning
confidence: 99%
“…Pomegranate (Punica granatum) has high antioxidant activity. This is attributed to its anthocyanins content such as delphinidin, cyanidine and pelargonidine, and ellagitannins (Budak, 2015). Sour cherry has rich bioactive content (e.g.…”
Section: Titration Aciditymentioning
confidence: 99%